Photothermal excitation of microcantilevers in liquid: effect of the excitation laser position on temperature and vibrational amplitude. (1st November 2013) - Bircher, Benjamin Andreas; Duempelmann, Luc; Lang, Hans Peter; Gerber, Christoph; Braun, Thomas
Abstract : Demands to improve the sensitivity and measurement speed of dynamic scanning force microscopy and cantilever sensing applications necessitate the development of smaller cantilever sensors. As a result, methods to directly drive cantilevers, such as photothermal or magnetic excitation, are gaining in importance. Presented is a report on the effect of photothermal excitation of microcantilevers on the increase in steady‐state temperature and the dynamics of higher mode vibrations. First, the local temperature increase upon continuous irradiation with laser light at different positions along the cantilever was measured and compared with finite element analysis data. The temperature increase was highest when the heating laser was positioned at the free end of the cantilever. Next, the laser intensity was modulated to drive higher flexural modes to resonance. The dependence of the cantilever dynamics on the excitation laser position was assessed and was in good agreement with the analytical expressions. An optimal position to simultaneously excite all flexural modes of vibration with negligible heating was found at the clamped end of the cantilever. The reports findings are essential for optimisation of the excitation efficiency to minimise the rise in temperature and avoid damaging delicate samples or functionalisation layers.